"Your Momma’s So Fat": An Exploration of Fat Pregnancy and Early Motherhood - Ioannoni, Kelsey (Canadian Woman Studies/les cahiers de la femme, 2023)
In 2020 I became a ‘single mother by choice’, or a solo parent. To get pregnant, I used a sperm donor and a process called Intrauterine Insemination, which is a procedure done by a fertility doctor. As a fat woman, the journey to get pregnant was not an easy one. My body size was a barrier to entry; I had to fight to be allowed to get pregnant. This paper explores my challenges in accessing fertility services as a ‘morbidly obese’ woman, the realities of being pregnant at my size, and some of the joys associated with being a fat mom. Throughout the essay, I employ the rhetoric of ‘your momma’s so fat’, a form of insult-based comedy that attacks both motherhood and fatness, and explore the fears I had around being a mom who is, in fact, so fat.